Non‐canonical AUX/IAA protein IAA33 competes with canonical AUX/IAA repressor IAA5 to negatively regulate auxin signaling. (16th October 2019) - Lv, Bingsheng; Yu, Qianqian; Liu, Jiajia; Wen, Xuejing; Yan, Zhenwei; Hu, Kongqin; Li, Hanbing; Kong, Xiangpei; Li, Cuiling; Tian, Huiyu; De Smet, Ive; Zhang, Xian‐Sheng; et al.
Abstract: The phytohormone auxin controls plant growth and development via TIR1‐dependent protein degradation of canonical AUX/IAA proteins, which normally repress the activity of auxin response transcription factors (ARFs). IAA33 is a non‐canonical AUX/IAA protein lacking a TIR1‐binding domain, and its role in auxin signaling and plant development is not well understood. Here, we show that IAA33 maintains root distal stem cell identity and negatively regulates auxin signaling by interacting with ARF10 and ARF16. IAA33 competes with the canonical AUX/IAA repressor IAA5 for binding to ARF10/16 to protect them from IAA5‐mediated inhibition. In contrast to auxin‐dependent degradation of canonical AUX/IAA proteins, auxin stabilizes IAA33 protein via MITOGEN‐ACTIVATED PROTEIN KINASE 14 (MPK14) and does not affect IAA33 gene expression. Taken together, this study provides insight into the molecular functions of non‐canonical AUX/IAA proteins in auxin signaling transduction. Synopsis: IAA33, a non‐canonical AUX/IAA without typical domains I and II, negatively regulates auxin response through the competition with IAA5, a canonical AUX/IAA, and thus releases the repression of ARF10/16. Furthermore, auxin stabilizes the IAA33 protein through interaction with MPK14 without influencing its transcription. IAA33 negatively regulates auxin responses and root stem cell identity. IAA33 regulates auxin signaling through competition with IAA5 for ARF10/16 binding. Auxin activates the phosphorylation activity of MPK14. Auxin induces IAA33 accumulation through phosphorylation by MPK14. Abstract : In contrast to other AUX/IAA‐family repressor, IAA33 is stabilised by auxin and competes with canonical IAA5 for binding to downstream auxin response factors ARF10/16.